Incentive contracts for politicians: a viable supplement to democracies? - Liessem, Verena (SSRN, 2003)
When reelection is uncertain, the election mechanism may provide insufficient incentives to politicians to implement the socially desirable policy. In this paper, we show that incentive contracts which the candidates offer themselves during the campaign can help to alleviate the problem even if the preferences of the candidates are unknown to the public. An incentive contract stipulates a policy space in which the implemented policy must lie in order that an elected candidate has the right to stand for reelection
Nach Informationen von SSRN wurde die ursprüngliche Fassung des Dokuments September 2003 erstellt